Total-dose effects on power mosfet in sepic converter for nanosatel-lite applications - Krishnamurthy, S. (Bentham Science Publishers, 2020)
Background: Power converters used in nanosatellite application required to be more tol-erant to radiations including proton, electron and heavy-ion radiation. Methods: A Single-Ended Primary Inductance Converter (SEPIC) is selected for the nanosatellite application because of the availability to step up and down the input voltage as well as having a non-inverting polarity between the input and output voltage. In this paper, remodeled SEPIC converter proposed with an improved performance at radiation environment to work for nanosatellite application. In addition, the analysis is carried out for the irradiated power MOSFET in SEPIC converter to check its impact on converter behavior. Results: Experiments conducted with the help of power MOSFET switch used in converter, irradiated with Cobalt60 gamma ray dose level from 50krad to 300krad and output characteristics ana-lyzed by chancing the duty cycle of converter. Investigations shown that conventional converter output characteristics were virtually constant from 10 to 60 duty cycle when different radiated MOSFETs used in the converter. Conclusion: The electrical characteristics started to fluctuate at 60 duty cycle and onwards, while the remodeled converter circuit was less distorted when increasing the radiation dose. Â© 2020 Bentham Science Publishers.